The role of fiberoptic endoscopic evaluation of swallowing in the assessment of pediatric dysphagia - M. Ahmed-Abdelhamid; Sally A. Sarwat (The Egyptian Journal of Otolaryngology, 2016)
En Abstract Background Swallowing is a basic, life-sustaining function that involves interplay between two distinct but related phenomena, airway protection and bolus transport. Pediatric dysphagia is one of the most important symptoms to be assessed and managed. The standard fiberoptic endoscopic evaluation of swallowing (FEES) protocol of Langmore (2001) was designed to assess dysphagia on all populations. Aim The aim of this work was to clarify the role of FEES in the diagnosis of pediatric dysphagia and the signs related to it. Study design This was a retrospective study that was conducted to assess pediatric dysphagia using FEES as a clinical diagnostic tool. Participants and methods The study included 64 children (38 male, 26 female). Of them, 32 patients were suffering from difficulty in swallowing of different degrees and 32 were controls (they were not suffering from any difficulty in swallowing). The mean age in months for symptomatic children was 41.47 ± 36.25 and the mean age in months for control cases was 42.08 ± 35.61. The examination was carried out using FEES applying the standard FEES protocol of Langmore (2001). Results Application of the standard FEES protocol of Langmore (2001) showed highly related signs of pediatric dysphagia, such as handling of secretions, pharyngeal function in part I and timing of the bolus flow/initiation of the swallow, structural movements during the swallow, and residue after the swallow and between swallows in part II. Conclusion and recommendation There are more common signs related to pediatric dysphagia than others and should be considered in any therapeutic program for overcoming dysphagia in children. Laryngomalacia is a structural disorder causing pediatric dysphagia in a considerable number of children. The standard FEES protocol should be applied on a larger number of pediatric populations with different disorders.